2017
DOI: 10.1002/star.201700082
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical properties, structural properties, and in vitro digestibility of pea starch treated with high hydrostatic pressure

Abstract: The influence of high hydrostatic pressure (HHP) treatment at 150, 300, 450, and 600 MPa for 25 min on the physicochemical properties, structural properties, and in vitro digestibility of pea starch was studied. Compared to native and pea starch treated at 150-450 MPa, the morphology of pea starch at 600 MPa was completely destroyed and the particle size became larger, indicating complete gelatinization. The X-ray diffraction results showed that the native pea starch was gradually changed from the C-type into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 34 publications
7
33
0
Order By: Relevance
“…The CV values of yellow pea and red lentil extrudates produced by N 2 gas injection method were found to be higher than the values achieved with the conventional extrusion process and the differences were mostly significant ( P < 0.05). Higher amounts of soluble starch were probably produced in extrudates with N 2 gas injection, due to the higher gas pressure (300 kPa) in the barrel, resulting in higher cold viscosity values, in line with results obtained for high hydro static pressure treatments of barley and pea starch, albeit at much lower pressures.…”
Section: Resultssupporting
confidence: 93%
“…The CV values of yellow pea and red lentil extrudates produced by N 2 gas injection method were found to be higher than the values achieved with the conventional extrusion process and the differences were mostly significant ( P < 0.05). Higher amounts of soluble starch were probably produced in extrudates with N 2 gas injection, due to the higher gas pressure (300 kPa) in the barrel, resulting in higher cold viscosity values, in line with results obtained for high hydro static pressure treatments of barley and pea starch, albeit at much lower pressures.…”
Section: Resultssupporting
confidence: 93%
“…Alterations in starch gelatinization properties on nanoscopic scale can be visualized using differential scanning calorimetry. In starch–water suspensions, a destruction of starch crystallinity was already determined by differential scanning calorimetry (DSC) and X-ray method [ 24 ]. These results coincide with findings in these studies, despite the significant lower moisture content in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…, < 30 min) (Leite et al., 2017). Although HHP has shown discrepant impacts on the gelatinization and pasting behaviors of pulse starches, most previous studies have revealed that the applied high pressure is able to induce partial gelatinization, thus lowering the gelatinization ΔH of the modified starches (Ahmed et al., 2016; Leite et al., 2017; Liu et al., 2018).…”
Section: Modifications Of Pulse Starchesmentioning
confidence: 99%